A new achromatic glass for near infrared laser instruments - Al-Hamdani, Ali H. (Iraqi Journal of Laser, 2009)
This research investigates new glasses which are best suitable for design of optical systemsworking in the infrared region between 1.01 to 2.3μm. This work is extended to Oliva & Gennari(1995,1998) research in which they found that the best known achromatic pairs are (BAF2-IRG2; SRF2-IRG3; BAF2-IRG7; CAF2-IRGN6; BAF2-SF56A and BAF2-SF6). Schott will most probably stop theproduction of these very little used and commercially uninteresting IRG glasses. In this work equallygood performances can be obtained by coupling BAF2, SRF2&CAF2 with standard glasses from Schottor Ohara Company. The best new achromatic pairs found are (SRF2-S-TIH10; CAF2-S-LAL9; CAF2-SLAL13and CAF2-S-BAH27). These new achromatic pairs are analyzed by using ZEMAX ray tracingprogram to design and analyze the same F/2 camera used by Oliva and for the same near infrared region(1.01-2.3μm). The results show that these pairs of glass have good performance in infrared designapplications.